Plasma p‐tau181/Aβ1‐42 ratio predicts Aβ‐PET status and correlates with CSF‐p‐tau181/Aβ1‐42 and future cognitive decline. Issue 1 (25th November 2022) - Fowler, Christopher J.; Stoops, Erik; Rainey‐Smith, Stephanie R.; Vanmechelen, Eugeen; Vanbrabant, Jeroen; Dewit, Nele; Mauroo, Kimberley; Maruff, Paul; Rowe, Christopher C.; Fripp, Jurgen; Li, Qiao‐Xin; Bourgeat, Pierrick; et al.
Abstract: Background: In Alzheimer's disease (AD), plasma amyloid beta (Aβ)1‐42 and phosphorylated tau (p‐tau) predict high amyloid status from Aβ positron emission tomography (PET); however, the extent to which combination of these plasma assays can predict remains unknown. Methods: Prototype Simoa assays were used to measure plasma samples from participants who were either cognitively normal (CN) or had mild cognitive impairment (MCI)/AD in the Australian Imaging, Biomarkers and Lifestyle (AIBL) study. Results: The p‐tau181/Aβ1‐42 ratio showed the best prediction of Aβ‐PET across all participants (area under the curve [AUC] = 0.905, 95% confidence interval [CI]: 0.86–0.95) and in CN (AUC = 0.873; 0.80–0.94), and symptomatic (AUC = 0.908; 0.82–1.00) adults. Plasma p‐tau181/Aβ1‐42 ratio correlated with cerebrospinal fluid (CSF) p‐tau181 (Elecsys, Spearman's ρ = 0.74, P < 0.0001) and predicted abnormal CSF Aβ (AUC = 0.816; 0.74–0.89). The p‐tau181/Aβ1‐42 ratio also predicted future rates of cognitive decline assessed by AIBL Preclinical Alzheimer Cognitive Composite or Clinical Dementia Rating Sum of Boxes ( P < 0.0001). Discussion: Plasma p‐tau181/Aβ1‐42 ratio predicted both Aβ‐PET status and cognitive decline, demonstrating potential as both a diagnostic aid and as a screening and prognostic assay for preclinical AD trials.